2019
DOI: 10.5194/angeo-2019-126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Performance of the IRI-2016 at the Brazilian low-latitude ionosphere over the South America Magnetic Anomaly during solar minimum

Abstract: Abstract. In this work we analyse the ionograms obtained by the recent Digisonde installed in Santa Maria (29.7º S, 53.7º W, dip angle = − 37º), Brazil, to calculate the monthly averages of the F2 layer critical frequency (foF2), its peak height (hmF2), and the E-region critical frequency (foE) acquired during geomagnetically quiet days from September 2017 to August 2018. The monthly averages are compared to the 2016 version of the International Reference Ionosphere (IRI) model predictions in order to study it… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…Uncertainties in h m F 2 estimates can reach several tens of kilometers making it is impossible to decide which model is better. Similar researches made by Zhao et al (2017) and Moro et al (2019) show that SHU-2015 option when using IRI-2016 to model h m F 2 over the Chinese and Brazilian regions is preferred. On the other hand, this conclusion is in sharp contrast with the results of an investigation carried out by Oyekola (2019).…”
Section: Resultssupporting
confidence: 66%
“…Uncertainties in h m F 2 estimates can reach several tens of kilometers making it is impossible to decide which model is better. Similar researches made by Zhao et al (2017) and Moro et al (2019) show that SHU-2015 option when using IRI-2016 to model h m F 2 over the Chinese and Brazilian regions is preferred. On the other hand, this conclusion is in sharp contrast with the results of an investigation carried out by Oyekola (2019).…”
Section: Resultssupporting
confidence: 66%
“…Zhao et al (2017) suggested SHU2015 over China, followed by BSE1979, regardless of the season and solar activity condition; after observing the worst performance by AMTB2013. The performance of the IRI-model over a low-latitude South American Ionospheric station was presented by Moro et al (2019). The authors suggested the use of the SHU2015 option during solar minimum.…”
Section: Current Studymentioning
confidence: 99%
“…The performance of the IRI‐model over a low‐latitude South American Ionospheric station was presented by Moro et al. (2019). The authors suggested the use of the SHU2015 option during solar minimum.…”
Section: Introductionmentioning
confidence: 99%